“Tax on Faith.” The Analysis and Evaluation of the Proposals from the Petition of 9th June 2025 (supplemented on 20th June 2025) Regarding the Legislative Initiative to Introduce a Church Tax (P11-89/25) - Stępień, Jakub (Prawo Kanoniczne, 2026)
The problem addressed: On June 9, 2025, the Senate of the Republic of Poland received a petition requesting a legislative initiative to introduce a church tax (P11-89/25). The document was subsequently supplemented on June 20. The author of the petition proposes the introduction of a tax mechanism based on the german Kirchensteuer, which allows the collection of an 8% tax on the remuneration of an individual who has declared their affiliation with a given religious community in an certain declaration. On January 20, 2026, the Committee of Petitions decided to seek opinions on the subject matter from the Ministry of Finance and the Ministry of Internal Affairs and Administration. The aim of the research conducted: The aim of the research is the analysis of the content of the petition in terms of its compliance with the Constitution of 2nd April 1997. Methods: The author used the comparative law method, covering the analysis of rules of Polish and German law, and a legal-dogmatic method, related to the interpretation of the constitutional and statutory provisions. The results of the research: The analysis of the Petition of 9th June 2025 allowed for the formulation of the conclusion that the proposed solution remains inconsistent with the content of Article 25 par. 2-3, Article 32, Article 53 par. 7, Article 84 and Article 217 of the Constitution. The conclusions drawn from the research: Introducing tax mechanisms based on the obligation to disclose the religious view of the individual as a basis for inclusion as a subject of a certain tax remains impossible in the polish constitutional order.